$\renewcommand{\ge}{\geqslant}\renewcommand{\le}{\leqslant}$ $\newcommand{\pa}[1]{\left( #1 \right)}$

Let us take $\alpha > 0$, $x_1 := \alpha$ and for any $n \ge \mathbb{N}$, \begin{align*} \boxed{x_n := \sum_{s=1}^{n-1} x_{n-s} x_s,} \end{align*} There exist $\xi,c \in \mathbb{R}_+$, such that for any $n \in \mathbb{N}$, \begin{equation} x_n \le c (\xi \alpha)^n n^{-\frac 32}. \qquad\qquad (EQ1) \end{equation}

Two series are equivalent if their quotient goes to $1$ as $n \rightarrow +\infty$. Numerical evidence suggests that \begin{align*} \boxed{x_n \underset{\substack{n \rightarrow +\infty}}{\sim} \; c \; \frac{(\xi \alpha)^n}{n^{\frac 32}}} \end{align*} with $\xi = 4$ and $c = \frac{1}{\xi \sqrt{\pi}}$. Would anyone know how to prove this numerical evidence please ? It's a "Cauchy square" in some sense so I guess the series has already been studied ? The proof of (EQ1) below gives an idea of the mechanisms. With the $S_n$ in the proof, numerical evidence suggests that $S_n \underset{\substack{n \rightarrow +\infty}}{\sim} 5.2247 / n^{\frac 32}$.

Remark : Take $\beta$. If we can prove the numerical conjecture, then we can deduce that if $y_1 = \alpha$ and $y_n = \beta \sum_{s=1}^{n-1} y_{n-s} y_s$, then $y_n \underset{\substack{n \rightarrow +\infty}}{\sim} \; c (\xi \alpha \beta)^n n^{-\frac 32}$ with $c = \frac{1}{\beta \xi \sqrt{\pi}}$, just by renormalization $y_n = x_n/\beta$. In other words the case $\beta = 1$ implies the general case. We could have normalized to make $\alpha = 1$, but we cannot normalize such that both $\alpha$ and $\beta$ are equal to 1.

Proof of (EQ1)

Let us prove (EQ1) inductively. Take $n \in \mathbb{N}$, $n \ge 2$, such that for any $s \in \{1,\dots,n-1\}$, $x_s \le c (\xi\alpha )^s s^{-\frac 32}$. Then \begin{align}\label{eq:bound_xn_interm} x_n \le c^2 \pa{\xi\alpha}^n \sum_{s=1}^{n-1} \frac{1}{\pa{s(n-s)}^{\frac 32}} = c^2 \pa{\xi\alpha}^n S_n, \end{align} where for any $x \in ]0,n[$ we define $g(x) := \pa{x(n-x)}^{-\frac 32}$ and want to estimate $S_n := \sum_{s=1}^{n-1} g(s)$ for any $n \ge 2$. By Carlo and Henri, we have $n^{3/2} S_n \rightarrow 2 \zeta(3/2) \simeq 5.2247$, we can also show easily that $S_n \le \frac{\xi}{n^{\frac 32}}$ where $\xi = 10$. Then we have \begin{align*} x_n \le ( \xi c) c (\xi \alpha)^n n^{-\frac 32}. \end{align*} We take $c = 1/\xi$ and the recursive equation is proved. Now for $n=1$ the right hand side of (EQ1) is $\alpha$ so the initial step is also valid.

Where does the "4" (of the numerical insight) could come from ? One possible starting point is presented here.

The function $g$ is decreasing on $]0,n/2]$, increasing on $[n/2,n[$, and for any $x \in ]0,n/2]$, $g(n-x) = g(x)$. By a series/integral comparision, we have \begin{align*} \int_1^{n-1} g \le S_n - g\pa{\frac n2}, \qquad S_n + g\pa{\frac n2} \le g(1) + g(n-1) + \int_1^{n-1} g \end{align*} when $n \in 2 \mathbb{N}$ and \begin{align*} \int_1^{n-1} g \le S_n - g\pa{\frac{n-1}{2}}, \qquad S_n + g\pa{\frac n2} \le g(1) + g(n-1) + \int_1^{n-1} g \end{align*} when $n \in 2 \mathbb{N} +1$, hence for all $n\in \mathbb{N}$ such that $n \ge 2$, \begin{align*} \int_1^{n-1} g \le S_n \le \frac{2}{(n-1)^{\frac 32}} + \int_1^{n-1} g. \end{align*} Defining $G(x) := \frac{n-2x}{\sqrt{x(n-x)}}$ we have $G'(x) = -\frac{n^2}{2} g(x)$ so \begin{align*} \int_1^{n-1} g = \frac{2}{n^2} \pa{G(1) - G(n-1)} = \frac{4 (n-2)}{n^2\sqrt{n-1}} \underset{\substack{n \rightarrow +\infty}}{\sim} \; \frac{4}{n^{\frac 32}}. \end{align*} For any $n \ge 2$, $\frac{n-2}{\sqrt{n-1}} \le \sqrt{n}$ so $\int_1^{n-1}g \le 4 n^{-\frac 32}$ and \begin{align*} \frac{4}{n^{\frac 32}} \pa{1 - \frac{2}{n} } \le S_n \le \frac{6}{n^{\frac 32}} \pa{1 + \frac{2}{n} }. \end{align*}

  • $\begingroup$ $\gamma=1/\sqrt{\pi}$. $\endgroup$ Commented Apr 8 at 15:41
  • $\begingroup$ Indeed, verified to relative precision $10^{-3} $, thanks ! $\endgroup$
    – Raphaël
    Commented Apr 8 at 15:52

2 Answers 2


You can reduce the evaluation of $S_n$ to a quadrature by means of the Abel-Plana formula, $$S_n=\sum _{s=1}^{n-1} g(s)=\int_1^{n-1}g(s)\,ds+\tfrac{1}{2}g(1)+\tfrac{1}{2}g(n-1)$$ $$\qquad\qquad -\,2\operatorname{Im}\int_0^\infty \frac{g(1+i y)-g(n-1+i y)}{e^{2 \pi y}-1}\,dy$$ $$\qquad=\frac{5n^2-12n+8}{(n-1)^{3/2} n^2}-4\operatorname{Im}\int_0^\infty \frac{g(1+i y)}{e^{2 \pi y}-1}\,dy,$$ where $g(s)=[s(n-s)]^{-3/2}=g(n-s)$.

The integral can be expanded in a power series in $n$, to leading order I find $$\lim_{n\rightarrow\infty} n^{3/2}S_n=5-4\operatorname{Im}\int_0^\infty \frac{(1+iy)^{-3/2}}{e^{2\pi y}-1}\,dy=5.224751\cdots$$ I don't think this integral has a closed-form expression.


Thanks to Carlo, using Abel--Plana once again one finds the simple formula $$\lim_{n\to\infty}n^{3/2}S_n=2\zeta(3/2)$$

  • $\begingroup$ wow, so this integral does have a closed form expression, cool! $\endgroup$ Commented Apr 8 at 18:36
  • $\begingroup$ @CarloBeenakker: well, whether $\zeta(3/2)$ is a "closed form expression" is debatable, no? $\endgroup$ Commented Apr 9 at 1:01

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service and acknowledge you have read our privacy policy.

Not the answer you're looking for? Browse other questions tagged or ask your own question.